Carers' perspectives of a weight loss intervention for adults with intellectual disabilities and obesity: a qualitative study. (28th February 2012) - Spanos, D.; Hankey, C. R.; Boyle, S.; Koshy, P.; Macmillan, S.; Matthews, L.; Miller, S.; Penpraze, V.; Pert, C.; Robinson, N.; Melville, C. A.
Abstract Background To date, no studies have explored the role of carers in supporting adults with intellectual disabilities (ID) and obesity during a weight loss intervention. The present study explored perceptions of carers supporting adults with ID, as they participated in a 6‐month multi‐component weight loss intervention (TAKE 5). Methods Semi‐structured interviews were used to explore the experiences of 24 carers. The transcripts were analysed qualitatively using thematic analysis. Results Three themes emerged from the analysis: carers' perceptions of participants' health; barriers and facilitators to weight loss; and carers' perceptions of the weight loss intervention. Data analysis showed similarities between the experiences reported by the carers who supported participants who lost weight and participants who did not. Lack of sufficient support from people from the internal and external environment of individuals with ID and poor communication among carers, were identified as being barriers to change. The need for accessible resources tailored to aid weight loss among adults with ID was also highlighted. Conclusion This study identified specific facilitators and barriers experienced by carers during the process of supporting obese adults with ID to lose weight. Future research could utilise these findings to inform appropriate and effective weight management interventions for individuals with ID.